Natural Products: A Rich Source of Antiviral Drug Lead Candidates for the Management of COVID-19 - Wijayasinghe, Yasanandana S.; Bhansali, Pravin; Viola, Ronald E.; Kamal, Mohammad A.; Poddar, Nitesh K. (Current Pharmaceutical Design, 2021)
Today, the world is suffering from the pandemic of a novel coronavirus disease (COVID-19), a respiratory illness caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This pandemic is the third fatal coronavirus outbreak that has already occurred in the 21st century. Even six months after its emergence, hundreds of thousands of people are still being infected with SARS-CoV-2, and thousands of lives are lost every day across the world. No effective therapy has been approved to date for the treatment of this disease, suggesting the need to broaden the scope in the search for effective treatments. Throughout history, folk medicine has been successfully used to treat various ailments in humans, and Traditional Chinese Medicine has been instrumental in the containment of a number of viral diseases. Owing to their high chemical diversity and safety profiles, natural products offer great promises as potentially effective antiviral drugs. In recent years, a large number of anti-coronaviral phytochemicals with different mechanisms of action have been identified. Among them, tetra-O-galloyl-β-D-glucose, caffeic acid, and saikosaponin B2 block viral entry. A number of flavonoids inhibit viral proteases. Silvestrol inhibits protein synthesis. Myricetin and scutellarein inhibit viral replication. Emodin, luteolin, and quercetin demonstrate anti-coronaviral activity by inhibiting multiple processes in the virus life cycle. In this review, we critically evaluate the findings of the natural product-based anticoronaviral research that has been published during the last two decades, and attempt to provide a comprehensive description about their utility as potential broad-spectrum anti-coronaviral drugs, examining leads that may guide/facilitate anti-SARS-CoV-2 drug development studies.
Keywords: SARS-CoV-2